Substitusi Tepung Labu Kuning Terhadap Elongasi Dan Daya Terima Mie Basah - Purnamasari, Fitri Asri; , Eni Purwani, S.Si., M.Si; , Rusdin Rauf, S.TP., M.P (2014)
Backround : Noodles is one type of staple to substitute rice. People get noodles so easy in everywhere because it's their favorite dish, cheap, easy to make. Wheat flour does not contain β-karoten so that the need for substitution pumpkin flour on noodles. Noodles with flour of yellow pumpkin can influence elongation and acceptability. Purpose : The purpose of this observation is analysis how flour of yellow pumpkin's influence to elongation and acceptability. Method: This method of this study is completely randomize design that use four additional variations (0%,10%,20% and 30%). Statistic analysis to elongation and acceptability use one way ANOVA with rate of significant 95%. If this analysis has influence, it will tested again by duncan multiple range test (DMRT). Result : The result of this observation is flour of yellow pumpkin influence elongation of wet noodles. Substitute yellow pumpkin flour's 0% and 10% give high elongation to noodles. Wet noodles with substitute 10% is panelists favored. Conclution : There are influence from substitute flour of yellow pumpkin in wet noodles to elongation and acceptability. Suggestion : Based on highest panelists acceptance, the suggest is substitute flour of yellow pumpkin 10% make wet noodles.